Report on Global Environmental Competitiveness (2013) - Jianping, Li; Minrong, Li; Jinnan, Wang; Jianjian, Li; Hongwen, Su; Maoxing, Huang (Current Chinese Economic Report Series, 2014)
Environmental Economics; Climate Change/Climate Change Impacts; Green Development; Environmental Competitiveness; Environmental Coordination; Economy Transformation; Environmental Carrying; Environmental Management